DOGECOIN PRICE ANALYSIS AND COST PER TRANSACTION ON DOGECOIN CRYPTO ASSET INVESTMENT DECISIONS - Marda lena; WIDYAWATI WIDYAWATI (Indragiri Research Center (ingreat), 2023)
Research conducted at the Indonesian Dogecoin Forum with the aim of knowing the effect of Dogecoin Prices and Costs per Transaction on Dogecoin Crypto Asset Investment Decisions. The population in this study are members of the Indonesian Dogecoin Forum who invest in Dogecoin Crypto. The approach used in this study is a quantitative approach using non-probability sampling techniques, as a sampling technique with purposive sampling of 50 respondents. With data collection techniques through questionnaires and data analysis using the SPSS version 26 program. Data analysis in this study used Descriptive Statistical Test, Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination, t test and f test. The results of the data analysis show that there is an influence of the Dogecoin Price and Cost per Transaction on Dogecoin Crypto Asset Investment Decisions. From the test results of the coefficient of determination, it can be seen that R Square(R2) is 46.3%. This shows that the Investment Decision variable is influenced by 2 independent variables, namely Dogecoin Price and Cost per Transaction. And the remaining 53.7% is influenced by other variables not included in this study. From the t test and f test it proves that the Dogecoin Price (X1) and Cost per Transaction (X2) variables have a positive and significant effect on the Investment Decision (Y) Dogecoin Crypto Asset.